Paclitaxel Plasma Concentration after the First Infusion Predicts Treatment-Limiting Peripheral Neuropathy - Hertz, Daniel L.; Kidwell, Kelley M.; Vangipuram, Kiran; Li, Feng; Pai, Manjunath P.; Burness, Monika; Griggs, Jennifer J.; Schott, Anne F.; Van Poznak, Catherine; Hayes, Daniel F.; Lavoie Smith, Ellen M.; Henry, N. Lynn (Clinical cancer research, 2018)
Purpose: Paclitaxel exposure, specifically the maximum concentration (Cmax) and amount of time the concentration remains above 0.05 μmol/L (Tc>0.05), has been associated with the occurrence of paclitaxel-induced peripheral neuropathy. The objective of this study was to validate the relationship between paclitaxel exposure and peripheral neuropathy. Experimental Design: Patients with breast cancer receiving paclitaxel 80 mg/m2 × 12 weekly doses were enrolled in an observational clinical study (NCT02338115). Paclitaxel plasma concentration was measured at the end of and 16–26 hours after the first infusion to estimate Cmax and Tc>0.05. Patient-reported peripheral neuropathy was collected via CIPN20 at each dose, and an 8-item sensory subscale (CIPN8) was used in the primary analysis to test for an association with Tc>0.05. Secondary analyses were conducted using Cmax as an alternative exposure parameter and testing each parameter with a secondary endpoint of the occurrence of peripheral neuropathy–induced treatment disruption. Results: In 60 subjects included in the analysis, the increase in CIPN8 during treatment was associated with baseline CIPN8, cumulative dose, and relative dose intensity (P < 0.05), but neither Tc>0.05 (P = 0.27) nor Cmax (P = 0.99). In analyses of the secondary endpoint, cumulative dose (OR = 1.46; 95% confidence interval (CI), 1.18–1.80; P = 0.0008) and Tc>0.05 (OR = 1.79; 95% CI, 1.06–3.01; P = 0.029) or Cmax (OR = 2.74; 95% CI, 1.45–5.20; P = 0.002) were associated with peripheral neuropathy–induced treatment disruption. Conclusions: Paclitaxel exposure is predictive of the occurrence of treatment-limiting peripheral neuropathy in patients receiving weekly paclitaxel for breast cancer. Studies are warranted to determine whether exposure-guided dosing enhances treatment effectiveness and/or prevents peripheral neuropathy in these patients. Clin Cancer Res; 24(15); 3602–10. ©2018 AACR.